HOW DOES CONSUMER ACCEPTANCE AFFECT PURCHASE INTENTION OF NEW PRODUCTS? - Rahmi, Mira; Hurriyanti, Ratih; Dirgantari, Puspo Dewi; Silalahi, Ira Valentina (Universitas Pamulang, 2021)
The rapid competition in the instant noodle food industry in Indonesia makes it difficult for new instant noodle products to enter the market. This study aims to analyze consumer acceptance of new products that affect purchase intentions. consumer innovation and consumer preferences are used to describe consumer acceptance of new instant noodle products. The method used in this study is a quantitative online questionnaire that collects data from 135 potential customers as instant noodle buyers. Regression analysis was used to analyze consumer acceptance as proxied by consumer innovation, quality and nutrition innovation, convenience, and marketing efforts. The results of this study indicate that consumer innovation, convenience, and marketing efforts, all three are said to have an influence on new product purchase intentions. Meanwhile, nutritional quality and innovation are said to have no effect. It is hoped that the results of this research can be used to contribute to the development of marketing concepts for new products on the market.